Validity of Biomarkers of Early Circulatory Impairment to Predict Outcome: A Retrospective Analysis - María Carmen Bravo; Paloma López-Ortego; Laura Sánchez; Rosario Madero; Fernando Cabañas; Fernando Cabañas; Armin Koch; Héctor Rojas-Anaya; Heike Rabe; Adelina Pellicer (Frontiers Media S.A., 2019)
Objectives: The definition of circulatory impairment in the premature infant is controversial. Current research suggests overdiagnosis and overtreatment. We aimed to analyse which biomarkers move clinicians to initiate cardiovascular treatment (CVT). The prognostic capacity for adverse outcome (death and/or moderate-severe brain damage by cranial ultrasound at term equivalent) of these biomarkers was evaluated.Study Design: Retrospective data analysis from preterm infants enrolled in a placebo-controlled trial on dobutamine for low superior vena cava (SVC) flow, who showed normal SVC flow within the first 24 h (not randomized). Five positive biomarkers were considered: MABP < gestational age (GA)-1 mmHg; MABP < GA-5 mmHg; lactate > 4 mmol/L; BE < −9 mmol/L; SVC flow <51 ml/kg/min.Results:Ninety eight infants formed the study cohort. Thirty six received CVT (2-95 h). Logistic regression models adjusted for gestational age showed a positive association between CVT and the risk of death or moderate-severe abnormal cranial ultrasound at term equivalent [(OR 5.2, 95%CI: 1.8-15.1) p = 0.002]. MABP < GA-1 mmHg and lactate > 4 mmol/L were the most prevalent biomarkers at start of treatment. Low BE, high serum lactate and low SVC flow at first echocardiography showed a trend toward being associated with adverse outcome, although not statistically significant.Conclusions: Low blood pressure and high lactate are the most prevalent biomarkers used for CVT prescription. Lactic acidosis and low SVC flow early after birth showed a trend toward being associated with adverse outcome. These findings support using a combination of biomarkers for inclusion in a placebo-controlled trial on CVT during transitional circulation.